2011
DOI: 10.1017/s0029665110004921
|View full text |Cite
|
Sign up to set email alerts
|

The conflicting effects of maternal nutrient restriction and early-life obesity on renal health

Abstract: Epidemiological and animal studies have demonstrated that early-life nutrition alters the metabolic responses and generates structural changes in complex tissues, such as the kidneys, which may lead to a reduction in the offspring lifespan. Independently, obesity induces a spontaneous low-grade chronic inflammatory response by modulating several of the major metabolic pathways that ultimately compromise long-term renal health. However, the combined effects of maternal nutrition and early-life obesity in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Likewise in obese adolescents, systolic ventricular function may be preserved but diastolic function may present evidence of impairment, which is associated by exercise intolerance [40]. These alterations could be explained, at least in part, by the effect of nutritional conditions on the development of the organs, as it has been reported that perinatal ambient has an important effect on the development of heart or kidney modifying the processes of apoptosis and cell survival [41].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise in obese adolescents, systolic ventricular function may be preserved but diastolic function may present evidence of impairment, which is associated by exercise intolerance [40]. These alterations could be explained, at least in part, by the effect of nutritional conditions on the development of the organs, as it has been reported that perinatal ambient has an important effect on the development of heart or kidney modifying the processes of apoptosis and cell survival [41].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, substantial evidence links IUGR with the aetiology of many chronic diseases in adult humans 15 . These findings have prompted extensive animal studies to identify the biological mechanisms for nutritional regulation of fetal growth and development as well as long‐term health consequences of IUGR, preterm birth, and other poor pregnancy outcomes 16–21 . This paper highlights the recent advances in this area of biomedical research, with a focus on effects of macronutrients and micronutrients on adverse pregnancy outcomes, including maternal morbidity and mortality, infant morbidity and mortality, as well as fetal and infant growth and development.…”
mentioning
confidence: 99%